Revisiting economies of scale: the moderating role of efficiency in corn farming - Zhang, Nianning; Zhang, Qing; Geng, Xianhui (Frontiers in Sustainable Food Systems, 2025)
IntroductionThis study extends prior work on economies of scale by introducing efficiency as a moderating factor in agricultural economies of scale. By incorporating regional heterogeneity, the paper provides a new framework for understanding scale expansion in diverse agricultural environments, offering insights that can guide policies for more sustainable agricultural production.MethodsThe study examines how efficiency affects economies of scale in corn production using data from the China Rural Revitalization Survey (CRRS). A double stochastic frontier model with two-stage least squares is employed to isolate efficiency loss and address scale endogeneity via instrumental variables.ResultsThe results reveal a significant U-shaped relationship between land operating scale and unit production cost. Insufficient efficiency under expanded scale increases costs, highlighting the need for sustainable resource allocation to balance productivity and long-term agricultural viability. Furthermore, efficiency moderates economies of scale, exhibiting regional heterogeneity.DiscussionThe policy implications include optimizing factor allocation through tiered management training, improving the land transfer market to reduce transaction costs, and deploying digital infrastructure and cross-regional service alliances to mitigate regional disparities. This study provides evidence on the role of managerial ability in efficiency, which optimizing economies of scale, demonstrating how resource efficient practices reduce input waste and align agricultural growth with ecological preservation. This study provides evidence that managerial ability in efficiency not only lowers production costs but also reduces resource waste, thereby supporting the dual goals of economic viability and environmental sustainability in agriculture. These insights inform policies to scale farming operations without compromising ecological integrity.